Gravity-model specification for tourism flows: The case of Albania - Visar Malaj (CES Working Papers, 2020)
The tourism sector plays a crucial role in economic growth of developing countries. Tourism increases business and employment opportunities and contributes to the development of local infrastructure. The preservation of cultural heritage and the promotion of peace between nations are other benefits of this sector. The main objective of this study is the investigation of the main demand and supply factors of international tourist arrivals to Albania, given the important role of the tourism sector on the national economy. A gravity-type equation is estimated through three different estimation techniques, controlling for basic and experimental independent variables. The basic assumption of the gravity model states that bilateral flows depend on some factors related to the origin and destination countries and other factors that approximate the bilateral distance. The analysis is based on an annual dataset of international tourist arrivals to Albania from 22 origin countries over the period 2001-2018. Empirical results show a satisfactory explanatory power of the considered equations.
Keywords: 330; international tourism; Albania; gravity model; panel data